Saudi-Iranian Relations Since the Fall of Saddam Rivalry, Cooperation, and Implications for U.S. Policy - Wehrey, Frederic (RAND Corporation, 2009)
This book surveys how Saudi-Iranian relations have unfolded in the Persian Gulf, Iraq, Lebanon, and Palestine since 2003, identifying the sources of rivalry and cooperation between the two powers. Understanding and leveraging this relationship will be a critical part of U.S. efforts to promote stability after the drawdown of U.S. forces in Iraq and to manage the regional impact of Iran's nuclear ambitions.